2013
DOI: 10.5539/ijms.v5n2p59
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Jordan Destination Image Using the Same Sample

Abstract: The aim of this paper is to track Jordan destination image using the same sample. The perceptions of tourists visiting Jordan on the pre-and post-visit images of Jordan were analysed. A total of 179 questionnaires were distributed by the assistance of tour guides who joined the tourists in their trip in Jordan. The distribution was accomplished into two stages for the same sample, in the first day of coming to Jordan, and in the last day of the trip during their way back to the airport. The results indicated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…(2010) on perceived destination image and destination choice intention of university student travellers to Mauritius found that ISs have an influence on perceived destination image and destination choice intention. Another study by Aloudat and Rawashdeh (2013) regarding Jordan destination image found two types of destination image as organic (mental) and induced (initial) images and discussed that initial destination image is shaped from the information achieved via commercial sources such as advertising companies and travel agencies, and also demonstrated that formation of destination image is influenced by IS.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…(2010) on perceived destination image and destination choice intention of university student travellers to Mauritius found that ISs have an influence on perceived destination image and destination choice intention. Another study by Aloudat and Rawashdeh (2013) regarding Jordan destination image found two types of destination image as organic (mental) and induced (initial) images and discussed that initial destination image is shaped from the information achieved via commercial sources such as advertising companies and travel agencies, and also demonstrated that formation of destination image is influenced by IS.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%